AN OPTICAL METHOD FOR MEASURING TEMPERATURE IN LABORATORY MODELS OF MANTLE PLUMES - Laudenbach N.; Christensen U.R. (My University, 2001)
We present a method for measuring radial temperature profiles in laboratory thermal plumes using the deflection of a laser beam that passes through the fluid. Plumes are created by injecting hot corn syrup into a column of cold syrup at a well-defined rate. Every second a new radial temperature profile can be taken, which makes the method suitable for monitoring time-dependent phenomena. We compare the thermal structure of stationary plume conduits and of propagating solitary waves with numerical results obtained with a 2-D axisymmetric convection code. The agreement is excellent and shows that accurate high-resolution temperature profiles can be obtained without perturbing the flow.
Keywords: NUMERICAL MODELS; THERMAL PLUMES; THERMOMETRY